Implementasi Ajaran Tri Hita Karana Oleh Penyuluh Agama Hindu Kepada Umat Hindu Di Desa Pakraman Asah Desa Pitra Kecamatan Penebel Kabupaten Tabanan - Ni Wayan Silawati (Purwadita : Jurnal Agama dan Budaya, 2020)
Peace and peace of mind are the desires of every creature, not only for the human race, but also for plants or plants and animals. Therefore peace is very important to be realized and it is hoped that all components of the nation will struggle, strive, and act for it to maintain and strengthen Unity in Diversity. Tri Hita Karana has the understanding of three causes of harmony, namely: the harmony of the relationship between humans and Hyang Widi Wasa (God Almighty), the harmony of relations between fellow human beings and the harmonious relationship between humanity and the natural environment. Based on the Decree of the Minister of Religion No. 516 the role of extension workers to guide and foster society with religious language. So it is important for extension workers, to understand the existing problems by providing education and understanding the concept of Tri Hita Karana. Extension agents need to improve their competence in the field of education, especially extension methods and strategies.  Keywords: Religious Instructor; Tri Hita Karana